2017
DOI: 10.1152/japplphysiol.00768.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypohydration on thermoregulatory responses in men with low and high body fat exercising in the heat

Abstract: This is the first known investigation to compare thermoregulatory responses to exercise heat stress between men with high and low body fat (BF) in a physiologically uncompensable environment while simultaneously examining the confounding influence of hydration status. Both groups demonstrated similar sweating and cutaneous vasodilatory responses when euhydrated, despite vast differences in rectal temperature. Furthermore, in contrast to low BF, individuals with high BF demonstrated similar increases in core bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…For example, there are well-appreciated deleterious effects of acute hypohydration including reduced exercise performance [3,4,10,12,13,14,16,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88], worsened mood [18,89,90,91], impaired cognitive function [19,20,21,91,92], altered thermoregulatory function [73,74,80,82,84,87,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108], and decreased glycemic regulation [11,109] (Figure 1). Chronic systemic hypohydration is a proposed pathogenic factor for hypertension, venous thromboembolism,...…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, there are well-appreciated deleterious effects of acute hypohydration including reduced exercise performance [3,4,10,12,13,14,16,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88], worsened mood [18,89,90,91], impaired cognitive function [19,20,21,91,92], altered thermoregulatory function [73,74,80,82,84,87,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108], and decreased glycemic regulation [11,109] (Figure 1). Chronic systemic hypohydration is a proposed pathogenic factor for hypertension, venous thromboembolism,...…”
Section: Clinical Relevancementioning
confidence: 99%
“…This hypothesis is supported by evidence that more methacholine chloride (an endothelium-dependent vasodilator) is required to achieve the drug concentration that provides half of the maximal response (EC 50 ) during hypohydration to ~2% body mass loss via exercise in the heat following fluid restriction compared to euhydration [25]. While only one [22] of these particular three studies examining vascular function [22,23,25] reported greater increases in body temperature in the hypohydrated state, several other studies have found hydration status to affect thermoregulatory function [73,74,80,82,84,87,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,134]. As a result, specific guidelines for hydration status have been set in certain populations, such as industrial workers in the heat [135], to minimize the potential for heat-stress and hypohydration-induced increases in cardiovascular strain and potential risk for adverse cardiovascular events.…”
Section: Vascular Health and Functionmentioning
confidence: 99%
“…Laboratory investigations have examined the effect of body fat on thermoregulation during exercise in the heat, but these studies are limited in number with small sample sizes with conflicting conclusions. 5,9,13,14 Some studies reported significant differences in Tcore and Tsk between high-body fat (Hi-BF) and low-body fat (Lo-BF) [15][16][17] where others suggest that there are no differences in any thermoregulatory outcome. [18][19][20][21] Moreover, individuals with higher body fat tend to have lower fitness levels, greater body mass and a smaller body surface area to mass ratio compared to those with lower body fat, which makes it difficult to ascertain the independent influence of body fat on thermoregulatory responses during exercise in the heat.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a paucity of data with obese individuals, some studies suggest obesity is linked with poorer cognitive performance compared to lean controls ( Boeka & Lokken, 2008 ; Lokken et al, 2009 ; Lokken et al, 2010 ). Poor cognitive performance may be exacerbated in obese individuals when heat stressed because of impaired thermoregulatory control ( Bar-Or, Lundegren & Buskirk, 1969 ; Buskirk, Bar-Or & Kollias, 1969 ; Tucker et al, 2017 ). However, the independent and combined effects of hyperthermia and hypohydration on cognition and mood in obese individuals have not been investigated.…”
Section: Introductionmentioning
confidence: 99%